2019
DOI: 10.1186/s13049-019-0631-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective pilot study using metabolomics discloses specific fatty acid, catecholamine and tryptophan metabolic pathways as possible predictors for a negative outcome after severe trauma

Abstract: Background We wanted to define metabolomic patterns in plasma to predict a negative outcome in severe trauma patients. Methods A prospective pilot study was designed to evaluate plasma metabolomic patterns, established by liquid chromatography coupled to mass spectrometry, in patients allocated to an intensive care unit (in the University Hospital Arnau de Vilanova, Lleida, Spain) in the first hours after a severe trauma ( n = 48). Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…In the light of Fong et al (1990) [40], it is possible to admit that alterations in lipid metabolism that are related to changes in cellular energy production during inflammatory response activation may be responsible for the elevated levels of myristic acid in the early stages of septic episode [7]. The question still to be answered is, however, 'why only this fatty acid, and not other shorter or longer chain fatty acid correlate with mortality', as already pointed out by Servià et al (2019) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of Fong et al (1990) [40], it is possible to admit that alterations in lipid metabolism that are related to changes in cellular energy production during inflammatory response activation may be responsible for the elevated levels of myristic acid in the early stages of septic episode [7]. The question still to be answered is, however, 'why only this fatty acid, and not other shorter or longer chain fatty acid correlate with mortality', as already pointed out by Servià et al (2019) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cambiaghi et al (2017) have observed a significant decrease of myristic acid in the plasma of non-responders to the septic shock treatment after 48 h [12]. Servià et al (2019) observed a significant correlation of increased myristic acid levels and mortality from severe trauma in a prospective metabolomic study including 48 trauma patients [13].…”
Section: Introductionmentioning
confidence: 96%
“…Our current understanding of the metabolic response to traumatic injury is based almost entirely upon the results of studies that have analysed serum samples acquired from patients at either a single post-injury time-point [20][21][22]24,43] or at multiple timepoints during the acute injury phase (days 1-7) [23,25,26,28,44,45]. Thus, via the analysis of blood samples obtained in the acute (days 0-4), intermediate (days [5][6][7][8][9][10][11][12][13][14] and late (days 15-112) post-injury phases, our study has provided novel insights into both the kinetics of the metabolic response to injury as well as the long-term metabolomic profiles of major trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is a systems-based approach for analysing low molecular weight metabolites present in cells, tissues or biofluids. Applying this analytical technique to serum or plasma samples acquired in the minutes [20], hour [21][22][23] and days [23][24][25][26] following combat injury, TBI or blunt/penetrative trauma has revealed significant traumainduced metabolic perturbations, with changes reported in glucose, fatty acid, amino acid and lipid metabolism. Showing promise as a diagnostic tool for mild TBI [27] and stratifying patients according to injury severity [22,23], metabolic profiling of the circulating metabolome has revealed unique signatures for patients with distinct clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Повышенные уровни производных сахара отражают нарушенный после ЧМТ церебральный метаболизм глюкозы, другие специфические метаболиты могут транспортироваться в поврежденный мозг для поддержания нормального метаболизма [3]. В качестве предикторов неблагоприятных исходов были предложены свободные жирные кислоты: декановая и октановая, вызывающие митохондриальную дисфункцию и окислительное повреждение липидов и белков [54], и мирамистиновая кислота, способная ингибировать выработку противовоспалительного интерлейкина-10 и повреждать клеточные мембраны, а также метаболиты катехоламинов и триптофана [55].…”
Section: Reviewsunclassified